2016
DOI: 10.1016/j.drugpo.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Scepticism and hope in a complex predicament: People with addictions deliberate about neuroscience

Abstract: Please cite this article as: Meurk, C., Morphett, K., Carter, A., Weier, M., Lucke, J., and Hall, W.,Scepticism and hope in a complex predicament: people with addictions deliberate about neuroscience, International Journal of Drug Policy (2016), http://dx.doi.org/10. 1016/j.drugpo.2016.03.004 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typeset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 30 publications
(38 reference statements)
4
15
0
1
Order By: Relevance
“…This suggests that a biomedical understanding of addiction to smoking, where nicotine induces neurochemical changes to the brain which make it very difficult to stop, does not dominate lay beliefs about addiction to cigarettes. These findings are consistent with previous research on how addicted individuals understand the biological basis of their addiction 15,[82][83][84] . While the physical aspects of addiction are often acknowledged, smokers' explanations of addiction are much broader, referring to the role of peers, routine, emotions, habits, inner strength or weakness, and contextual cues.…”
Section: Discussionsupporting
confidence: 82%
“…This suggests that a biomedical understanding of addiction to smoking, where nicotine induces neurochemical changes to the brain which make it very difficult to stop, does not dominate lay beliefs about addiction to cigarettes. These findings are consistent with previous research on how addicted individuals understand the biological basis of their addiction 15,[82][83][84] . While the physical aspects of addiction are often acknowledged, smokers' explanations of addiction are much broader, referring to the role of peers, routine, emotions, habits, inner strength or weakness, and contextual cues.…”
Section: Discussionsupporting
confidence: 82%
“…For example, these conceptual frameworks may engender genetic essentialism —the misguided view that DNA contains the biological, largely immutable “essence” of a disorder, inevitably consigning people with certain genes to the fate of developing a particular health problem (Dar-Nimrod & Heine, 2011; Haslam, 2011). Although the essentialist view that addiction results deterministically from genes may deflect individual blame by countering the notion that people with addictions are simply choosing freely to engage in problematic behaviors, it may also promote the notion that people with genetically caused disorders lack agency or control over their behavior, and are thus helpless against their symptoms (Dar-Nimrod, Zuckerman, & Duberstein, 2013; Kong, Dunn, & Parker, 2017; Meurk et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…These findings support other empirical research on public understandings of neuroscience which has found that neuroscience information is interpreted through the lens of alreadyexisting cultural worldviews and explanations of behaviour (Bröer & Heerings, 2012;Meurk et al, 2016;O'Connor & Joffe, 2013;Pickersgill et al, 2011). An issue deserving further research attention is the way that people conceptualise the link between their brain and behaviour.…”
Section: Lay Engagement With Neuroscience Informationsupporting
confidence: 79%
“…More specifically, it is hypothesised that it will lead addicted individuals to see their addiction as a medical problem requiring medical treatment. An increasing number of studies have investigated stakeholder knowledge and attitudes towards neurobiological technologies and their implications for various facets of human existence, including adolescence (Choudhury, McKinney, & Merten, 2012), mental illness (Borgelt, Buchman, & Illes, 2011;Bröer & Heerings, 2012;Pescosolido et al, 2010) and addiction Meurk et al, 2016;Netherland, 2011).…”
Section: Lay Beliefs About the Brain And Behaviourmentioning
confidence: 99%